2017
DOI: 10.1099/jgv.0.000808
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C virus in vitro replication is efficiently inhibited by acridone Fac4

Abstract: 18Hepatitis C Virus (HCV) affects about 170 million people worldwide. The current treatment has 19 a high cost and variable response rates according to the virus genotype. Acridones, a group of 20 compounds extracted from natural sources, showed potential antiviral actions against HCV. 21Thus, this study aimed to evaluate the effect of a panel of 14 synthetic acridones on the HCV life 22 cycle. The compounds were screened using an Huh7.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 50 publications
1
14
0
Order By: Relevance
“…This indirect data, together with molecular docking results, suggests that the observed replication inhibition was unlikely to be due to the direct inhibition of RNA polymerase activity. Similarly, our results demonstrated that FAM E3 did not intercalate with dsRNA, a mechanism of action described for compounds which inhibit HCV replication, another member of Flaviviridae family 45,46 .…”
Section: Discussionsupporting
confidence: 79%
“…This indirect data, together with molecular docking results, suggests that the observed replication inhibition was unlikely to be due to the direct inhibition of RNA polymerase activity. Similarly, our results demonstrated that FAM E3 did not intercalate with dsRNA, a mechanism of action described for compounds which inhibit HCV replication, another member of Flaviviridae family 45,46 .…”
Section: Discussionsupporting
confidence: 79%
“…To increase the yield and reduce the reaction time, a few drops of DMSO were added to accelerate the reaction successfully. The 1 H NMR spectra of 1,3-dimethoxy-N-methylacridone (1), 1,5-O,O-dimethylcitrusinine-I (2), 1-O-methylcitpressine-II (3), acronycine (4), 5-methoxyacronycine (5) and 1-O-methylcitracridone-II (6) were measured in CDCl3. Lanthanide-induced shift studies with Eu(dpm)3 were carried out with acridones 1-6.…”
Section: Resultsmentioning
confidence: 99%
“…Acridone alkaloids have become an important topic of medicinal chemistry research in recent years, due to the broadband biological activities on the tricyclic acridine ring system for different design and discovery [1,2]. There are numerous pharmacological publications of the acridone alkaloids and their derivatives that have been reported previously, including anticancer [3,4], antivirus [5][6][7], antibacterial and antifungal [7], anticonvulsant [1], anti-acetylcholinesterase [8], etc. These features are attributed to the semiplanar heterocyclic structure, which interacts with different biomolecular targets proved by the docking studies [9].…”
Section: Introductionmentioning
confidence: 99%
“…The acridone M14 was synthesized using protocols that were previously described by our group, with minor modifications (Campos et al ). A mixture of phloroglucinol (19 mmol), para ‐toluenesulphonic acid (0·5 mmol) and 13 mmol of 2‐amino‐3,4,5‐hydroxybenzoic acid, in 1‐hexanol (65 ml) was refluxed for 8 h. The heterogeneous mixture was stirred with cold hexane.…”
Section: Methodsmentioning
confidence: 99%